THE INFLUENCES OF NATHANIEL HAWTHORNE’S YOUNG GOODMAN BROWN ON BUDI DARMA’S BAMBANG SUBALI BUDIMAN: A COMPARATIVE LITERATURE - Mirotin Eka Wahyuningsih (Universitas Gadjah Mada, 2014)
The purpose of this article is to observe the influence of “Young Goodman Brown” on “Bambang Subali Budiman” applying Comparative Literature Study. The theme of Hypocrisy as the result of the journey of looking for evil inside is the universal values in both works. Although those works have similarities, some elements are different. Furthermore, the differences demonstrate the originality of “Bambang Subali Budiman” as influenced work. The study of Comparative Literature eliminates the gap between Western and Eastern literary works under the coverage of World Literature.